2010
DOI: 10.1590/s0365-05962010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica das lesões orais associadas a doenças dermatológicas

Abstract: BACKGROUND: Dermatologic diseases are not only represented by lesions affecting the skin but also by manifestations that may involve the mucous membranes, including oral mucosa. OBJECTIVES: To evaluate the frequency of oral manifestations associated with dermatologic diseases considering location and clinical characteristics of the lesions found and also gender, age and race of patients. METHOD: It was an observational, cross-sectional study of patients who sought for treatment at the Dermatology Service of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 18 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…20 Diagnosis is confirmed by histopathology, which reveals intraepidermal acantholytic blisters just above the basal layer. 6,14,21 With respect to frequency, this disease is characterized by being rare. According to Bystryn et al, it occurs in 0.75 to 5 cases per million individuals per year; however, these figures also depend on geographical location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Diagnosis is confirmed by histopathology, which reveals intraepidermal acantholytic blisters just above the basal layer. 6,14,21 With respect to frequency, this disease is characterized by being rare. According to Bystryn et al, it occurs in 0.75 to 5 cases per million individuals per year; however, these figures also depend on geographical location.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the blisters are taut, with serous and/or hematic contents and are situated over erythematous, urticarious or normal skin. 6,8,17,19,24 Schellinck et al estimate the incidence of BMMP at 1.5 to 9.6 new cases per 100,000 inhabitants per year. 25 In the present study, only 5 cases were found, with a greater prevalence in women and in individuals over 50 years of age, confirming reports found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in 2009, evaluated 88 patients with dermatological diseases and suggested the frequency of oral mucosal lesions was 35.7%. [8] Suliman et al . in 2001, observed the prevalence of oral mucosal lesions in patients with dermatological diseases was 57.9% in Sudanese population.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Umbelino Junior et al (2), in which the incidence of oral manifestations in SLE was assessed, a prevalence of oral lesions of 6.5% was observed, hairy leukoplakia in 3.7% and candidiasis in 20.0% of SLE cases. Although there is a frequency of oral lesions in SLE, overall, the specific prevalence of oral manifestations in females is low (47,49).…”
Section: Discussionmentioning
confidence: 99%